2021
DOI: 10.2967/jnumed.120.256230
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided High-Intensity Focused Ultrasound, A Novel Application for Interventional Nuclear Medicine?

Abstract: Image-guided high-intensity focused ultrasound (HIFU) has been increasingly used in medicine over the past few decades, and several systems for such have become commercially available. HIFU has passed regulatory approval for the ablation of various solid tumors, the treatment of neurological diseases, and the palliative management of bone metastases around the world. The mechanical and thermal effects of focused ultrasound provide a possibility for histotripsy, support radiation therapy, and targeted drug deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…In the past two decades, HIFU has been widely applied in the treatment of uterine fibroids [10]. HIFU is a non-invasive technique guided by magnetic resonance imaging (MRI) or ultrasound, which can achieve myoma ablation without damaging adjacent structures [11]. Numerous previous studies have confirmed the efficacy and safety of HIFU, with rapid symptom relief, short recovery time and reduced risk of complications [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, HIFU has been widely applied in the treatment of uterine fibroids [10]. HIFU is a non-invasive technique guided by magnetic resonance imaging (MRI) or ultrasound, which can achieve myoma ablation without damaging adjacent structures [11]. Numerous previous studies have confirmed the efficacy and safety of HIFU, with rapid symptom relief, short recovery time and reduced risk of complications [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The reference phase map was calculated by averaging 3 pre-heating phase maps. A correction for phase drift was applied [7,24]: drift was estimated from the average phase value in an ROI of 67 voxels in an unheated region in the gel of the phantom from the PRFS scans. The phase error due to drift was subtracted to correct the temperature change maps.…”
Section: Resultsmentioning
confidence: 99%
“…US imaging is cheap, portable, compatible with patient implants and its frame rate favourable for imaging moving organs [25]. MR imaging has excellent soft tissue differentiation, provides spatial guidance in the targeted area independently from the acoustic absorption and reflection of tissues (inside the skull, for example) and is able to monitor temperature intraprocedurally using temperature-dependent proton resonance frequency shift, T 1 temperature mapping, or diffusion temperature mapping [7].…”
Section: (High-intensity ) Focused Ultrasound For Cancer Therapy: a R...mentioning
confidence: 99%
See 2 more Smart Citations